2019
DOI: 10.33073/pjm-2019-056
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Drug Resistance, and Virulence of Staphylococcus aureus Isolated from Ocular Infections in Polish Patients

Abstract: Analysis of the epidemiology of Staphylococcus aureus (SA) ocular infections and virulence factors of the isolates with a special emphasis on their drug resistance, and the ability of biofilm formation. In a period from 2009 to 2013, 83 isolates of SA were prospectively collected and preserved in a multicenter laboratory-based study carried out in southern Poland. Epidemiological, phenotypic, and genotypic analyses were performed. The resistance and virulence genes were analyzed. Screening for the biofilm form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“… 76 Additionally, the prevalence of S. aureus virulence factors such as pvl , enterotoxin E ( sea ) or leucocidin E ( LukE ), among ocular isolates, have demonstrated that pvl and lukE were found in majority of ocular strains, whereas sea was less common. 78 , 79 However, a recent study showed that the enrichment of enterotoxin superantigens in S. aureus ocular strains when compared with nonocular S. aureus strains. 80 …”
Section: Discussionmentioning
confidence: 99%
“… 76 Additionally, the prevalence of S. aureus virulence factors such as pvl , enterotoxin E ( sea ) or leucocidin E ( LukE ), among ocular isolates, have demonstrated that pvl and lukE were found in majority of ocular strains, whereas sea was less common. 78 , 79 However, a recent study showed that the enrichment of enterotoxin superantigens in S. aureus ocular strains when compared with nonocular S. aureus strains. 80 …”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few literatures focusing on pediatrics. In the studies involving a broader age range (from infant to elderly), the percentage of MRSA varies a lot: the rates were high in the Ocular TRUST3 study (48.1%, 2007-2008) and the latest ARMOR study (20,24), both of which were conducted in United States; the rates were extremely low in Canada (6.4%, 2000-2010) and Polish (6.0%, 2009-2013) (25,26); and for surveys in Asia, a similar rate of 21% was demonstrated in India (2007-2017) (27), a higher rate of 56.8% in Shanghai (6 year study, uncertain) and 52.8% in Taiwan (1999-2008) (17,28), and a lower rate of 12.5% In Hong Kong (2005-2015) (18). In general, the rates of S. aureus cultured positive for MRSA over the world were variable depending on geography and year of study, and most of the rates were relatively high throughout the past two decades; more attention should be paid to it.…”
Section: Discussionmentioning
confidence: 99%
“…However, no difference of MRSA proportion was found in children under 1 year of age compared to those beyond, and MRSA colonized in conjunctival sac did not seem to cause severe ophthalmic infection to the newborn (4). Even so, conjunctival MRSA infection should not be underestimated in infants because the virulence of MRSA changes (26,30), and infants are extremely susceptible to bacterial infection due to their pre-matured immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multilocus sequence typing (MLST), which compares the genetic sequences of seven housekeeping genes (arcC, aroE, glpF, gmk, pta, tpi, and yqiL) to identify sequence types (STs), has revealed ST5, ST8, ST15, ST30, ST59, and ST772 as common among specific S. aureus ocular strain sets [13][14][15][16]. Additionally, studies to assess the prevalence of S. aureus virulence factors among ocular isolates such as Panton-Valentine Leukocidin (pvl), Enterotoxin E (sea) or Leukocidin E (lukE) have demonstrated that while pvl and lukE are found in the majority of sampled ocular strains, sea may be less common [16,17]. While this initial work has provided insight into the genetic characteristics of ocular S. aureus clinical isolates, they have largely been limited to small sample sizes and a handful of virulence factors.…”
Section: Introductionmentioning
confidence: 99%